Seed Coating: A Tool for Delivering Beneficial Microbes to Agricultural Crops - Rocha, Inês; Ma, Ying; Souza-Alonso, Pablo; Vosátka, Miroslav; Freitas, Helena; Oliveira, Rui S. (Frontiers in Plant Science, 2019)
Plant beneficial microbes (PBM), such as plant growth promoting bacteria (PGPB), rhizobia, arbuscular mycorrhizal (AM) fungi and Trichoderma can reduce the use of agrochemicals, increase plant yield, nutrition and tolerance to biotic-abiotic stresses. Yet, large-scale applications of PBM have been hampered by the high amounts of inoculum per plant or per cultivation area needed for successful colonization and consequently the economic feasibility. Seed coating, a process that consists in covering seeds with low amounts of exogenous materials is gaining attention as an efficient delivery system for PBM. Microbial seed coating comprises the use of a binder, in some cases a filler, mixed with inocula, and can be done using simple mixing-equipment (e.g. cement-mixer) or more specialized/sophisticated apparatus (e.g. fluidized bed). Binders/fillers can be used to extend microbial survival. The most reported types of seed coating are seed dressing, film coating and pelleting. Tested in more than 50 plant species with seeds of different dimensions, forms, textures and germination types (e.g. cereals, vegetables, fruits, pulses and other legumes), seed coating has been studied using various species of PGPB, rhizobia, Trichoderma and to a lesser extent AM fungi. Most of the studies regarding PBM applied via seed coating are aimed at promoting crop growth, yield and crop protection against pathogens. Studies have shown that coating seeds with PBM can assist crops in improving seedling establishment and germination or achieving high yields and food quality, under reduced chemical fertilization. The right combination of biological control agents (BCA) applied via seed coating can be a powerful tool against a wide number of diseases and pathogens. Less frequently, studies report seed coating being used for adaptation and protection of crops under abiotic stresses. Notwithstanding the promising results, there are still challenges mainly related with the scaling up from the laboratory to the field and proper formulation, including efficient microbial combinations and coating materials that can result in extended shelf-life of both seeds and coated PBM. These limitations need to be addressed and overcome in order to allow a wider use of seed coating as a cost-effective delivery method for PBM in sustainable agricultural systems.